2014
DOI: 10.1097/mao.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Otoprotective Properties of Mannitol Against Gentamicin Induced Hair Cell Loss

Abstract: Gentamicin ototoxicity is increasingly severe from the apex to basal turn of the cochlea. Treatment with mannitol prevents gentamicin-induced hair cell loss in a dose-dependent manner, protecting both IHCs and outer hair cells. Mannitol appears to act as a free radical scavenger to reduce the cytotoxic effects of gentamicin by reducing the level of oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…As expected, gentamicin-induced ototoxicity on OHCs was higher in the basal than in the middle or apical turns ( fig. 3 , table 1 ) as described in other studies [Cunningham et al, 2011;McDowell, 1982;Wood et al, 2014]. Our findings are in line with data obtained in auditory cell lines.…”
Section: Metformin Protects Hcs From Gentamicin-induced Toxicitysupporting
confidence: 83%
“…As expected, gentamicin-induced ototoxicity on OHCs was higher in the basal than in the middle or apical turns ( fig. 3 , table 1 ) as described in other studies [Cunningham et al, 2011;McDowell, 1982;Wood et al, 2014]. Our findings are in line with data obtained in auditory cell lines.…”
Section: Metformin Protects Hcs From Gentamicin-induced Toxicitysupporting
confidence: 83%
“…These findings support the hypothesis that VS-induced SNHL may result in part from TNF-α-containing tumor secretions passing into the cochlea via the internal auditory canal. The hypothesis that TNF-α may play a role in VS-induced SNHL comes from several studies showing that (a) VS tumor secretions contain high levels of TNF-α (20), (b) VS tumor size and proximity to the inner ear are poorly correlated with SNHL in VS patients (3), and (c) upregulation of TNF-α in the cochlea in response to a variety of etiologies of inner ear disease causes hearing loss (21)(22)(23)(24)(25)(42)(43)(44)(45)(46). Previous studies have shown upregulated levels of TNF-α following exposure to high levels of noise, implicating TNF-α in acoustic trauma (24,25,46).…”
Section: Discussionmentioning
confidence: 99%
“…Direct inoculation of cerebrospinal fluid with Streptococcus pneumoniae in Mongolian gerbil model led to an increase in TNF-α circulation that was directly associated with bacterial meningitis and elevations in auditory brainstem response (ABR) thresholds (23). Activation of TNFα is also observed in rodents treated with cisplatin (42,43) and gentamicin (44,45), both of which have known structural and functional ototoxic effects. Our findings contribute to this body of work by suggesting that the acute effects of TNF-α exposure on cochlear structure and function may be specific to synaptic degeneration and reduction in CAP amplitudes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may represent a very small quantity of fluid flow across the perforation despite no noticeable change in donor or receptor volumes during the experiment. If we assume ototoxicity from aminoglycosides applied directly to hair cells occurs with 10μM of compound (a documented ototoxic dose in explanted hair cells) then with the dosing regimen seen in this experiment applied to the RWM, an intact membrane would require 7 days to diffuse 10μM across the RWM while a membrane with a single microperforation of approximately 2.5 × 10 -3 mm 2 would require just under 5 hours 29 . Assuming minimal interaction between perforations, an increase in the number of perforations will inversely decrease the time necessary to achieve a target dose.…”
Section: Discussionmentioning
confidence: 99%